Analisis Unsur Etnomatematika dan Nilai Optimasi pada Produksi Alat Musik Angklung Bali - Eriska May Wulandari; Wayan Evi Handayani; Ni Made Audi Kirei Saraswati; Ni Kadek Dhirayani; I Gusti Ayu Made Srinadi (Journal on Education, 2024)
Geometry Calculations and Optimization Values are one form of application of Ethnomathematics that can be applied to the production of Balinese Gamelan Angklung Musical Instruments. The aim of this study is to determine the number of ethnomathematics elements that can be found in a culture in each region through a research project. The methodology for this study was carried out using direct observation and interviews by visiting the production site of Gamelan Angklung Musical Instruments on Gong Tari, precisely in Tihingan Village, Banjarangkan District, Klungkung Regency, Bali Province. The results of this study found that there were many geometric elements that could be found in Balinese Gamelan Angklung, apart from that, optimization values were also calculated in the production process. The conclusion of this study explains that many elements of ethnomathematics can be found in various cultures and regions, one of which is in the process of making Gamelan Angklung Musical Instruments on Gong Tari.